Organizational Change and Strategic Thinking - Folarin, Kehinde (Journal of Strategic Management, 2021)
In most organizations, the strategic planning process is an annual exercise at best. It ensures that leaders pause at some point to take stock in their organizations, look out over the horizon, assess the external environment and establish their team's priorities and goals. It's a valuable process. However, it doesn't typically happen frequently or fast enough to address the challenges and complexities of the present-day corporate world. That's why leaders with strategic thinking skills have the edge in navigating organizational change. This article addresses the current scenario and realities of organizations and proffered some recommendations.